Effects of Short Duration Omega-3 Based Fatty Acid Supplementation to Developing Heifers on Growth, Intake, and Reproduction - Megan C. Sollors (Kansas Agricultural Experiment Station Research Reports, 2026)
Objective: The objective of this study was to assess the effect of omega-3 fatty acid supplementation on body weight gain, feed intake, and reproductive efficiency in replacement heifers. Study Description: This two-year study (2024: 56 days, 2025: 68 days) at Kansas State University evaluated omega-3 supplementation on spring-born heifers. Heifers were assigned based on body weight and age to one of two treatments: non-supplemented control (NOSUPP, n = 39) or supplemented (SUPP, n = 46) with 0.48 - 0.72 lb/day dry matter basis of an extruded flaxseed and algae-based supplement designed to provide omega-3 fatty acids (Better Fed Foods/NBO3, Manhattan, KS). In 2024, NOSUPP had one diet, while in 2025, more than one base diet was fed due to ingredient availability and logistical constraints. Estrus was synchronized (Select Synch + controlled internal drug release + artificial insemination), and then heifers were exposed to Angus sires for ≥ 45 days. Body weight, intake, and pregnancy status were measured and analyzed in SAS. The Bottom Line: Omega-3 supplementation improved heifer growth, which increased total body weight gain and average daily gain. Reproduction was not statistically different, though pregnancy rates rose slightly, suggesting a possible added benefit.
Keywords: heifers; omega-3; supplementation